2008
DOI: 10.1002/aoc.1385
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity studies in the reaction between iodobenzene and phenylacetylene: Sonogashira coupling vs hydroarylation

Abstract: The selectivity of the coupling reaction between iodobenzene and phenylacetylene was evaluated. Several palladium catalysts, ligands and reaction conditions were tested, showing that supported catalysts, room temperature or ionic liquids (NHC precursors) favor Sonogashira coupling, while the non-supported ones, higher temperature and PPh 3 as ligand, favor hydroarylation. Neither excess of iodobenzene nor phenylboronic acids are required; and it is possible to avoid the use of PPh 3 , although this lowers sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…This corroborates our previous results of the role of ligands (PPh 3 vs NHC) in directing the selectivity to a Sonogashira reaction or an hydroarylation [31].…”
Section: Scheme 2 Reaction Between Haloarenes and Acetylenessupporting
confidence: 92%
See 3 more Smart Citations
“…This corroborates our previous results of the role of ligands (PPh 3 vs NHC) in directing the selectivity to a Sonogashira reaction or an hydroarylation [31].…”
Section: Scheme 2 Reaction Between Haloarenes and Acetylenessupporting
confidence: 92%
“…A mechanistic pathway for this kind of reaction was proposed by Wu [42] and by us [31] and comprised a Sonogashira coupling to furnish aryl-trimethylsilyl acetylene, a sila-Sonogashira coupling to furnish diarylacetylene, and finally an hydroarylation of the diarylacetylene with iodoarene to furnish triarylethylene. In this case EtOH serves as a source of hydrogen, and acetaldehyde is released.…”
Section: Scheme 2 Reaction Between Haloarenes and Acetylenesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this direction, researchers have immobilised Pd on solid supports such as activated carbon (charcoal) (Rossy et al, 2014) (Djakovitch and Rollet, 2004), metal oxides (Cwik, Hell and Figueras, 2006;Hosseini-Sarvar, Razmi and Doroodmand, 2014;Roy, Senapati and Phukan, 2015;Kotadia et al, 2014) (MgO, ZnO, TiO 2 , ZrO 2 , Fe 2 O 3 , CeO 2 , . ), clays (Borah and Dutta, (2013), alkaline earth salts (CaCO 3 , BaSO 4 , BaCO 3 , SrCO 3 ) (Barros et al, 2008) and organic polymers (Ye and Yi, 2008;Kim et al, 2007). However, the leaching of palladium from the catalyst is still the main problem, even though most researchers have reported that their catalysts can be recycled by the redeposition of Pd onto the support (Redon, Peña and Crescencio, 2014).…”
mentioning
confidence: 99%